Efektivitas Kinesio Taping terhadap Nilai Neck Disability Index pada Myofascial Pain Syndrome Otot Upper Trapezius: A Systematic Literature Review - Aisyah Yasmin Khoirunnisa; Iman Santoso (Pusat riset dan Inovasi Nasional, 2026)
Myofascial pain syndrome (MPS) in the upper trapezius muscle is one of the disorders commonly found in the neck area, characterized by myofascial trigger points (MTrP) in taut bands or tight muscle bands. Kinesio taping (KT) is a non-invasive therapy used in the management of MPS of the upper trapezius to improve neck disability measured using the Neck Disability Index (NDI). However, stronger evidence is still needed regarding the effectiveness of KT in reducing neck disability scores in MPS upper trapezius. This study aims to review and analyze the effectiveness of KT on NDI scores in MPS upper trapezius. The research method used is a systematic review employing PRISMA-P and the PICOS framework. The sample and population of the study consist of articles obtained from databases such as Crossref, Scopus, PubMed, Google Scholar, and Semantic Scholar. Keywords such as